TITIK KRITIS MANAJEMEN LABA PADA PERUBAHAN TAHAP LIFE CYCLE PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reva Meiliana Eli Misniasih (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This research was aimed at empirically proving the existence of the difference earning management critical point in the companies at the company life cycle stage listed in the Indonesian Stock Exchange. The variable consisted of accrual earnings management (discretionary accrual) as the dependent variable and as the independent variable was the company life cycle i.e. growth-mature and mature-stagnant. The sample of the study was the companies listed in IDX in the period of 2009-2015, by using purposive sampling method with independent testing samples t-test using SPSS version 21. Based on the result of testing showed that the life cycle growth-mature stage and life cycle mature–stagnant stage did not have a significant difference from the accrual earnings management (discretionary accrual).